Eficacia del proyecto “Una Vida Digna y Sin Violencia” de la ONG Paz y Esperanza en la promoción del derecho a una vida libre de violencia para mujeres con discapacidad de Lima Metropolitana y Callao, durante el periodo 2019 - 2022 - López Reategui, Mónica Jhoanna (2024)
The present thesis aims to assess the effectiveness of the project "A Dignified Life Without Violence" by the NGO Paz y Esperanza in promoting the right to a life free from violence for women with disabilities in Lima Metropolitan Area and Callao, during the period 2019-2022. The research is justified from a social management perspective due to its relevance in a context of increased violence against women with disabilities, aggravated by the COVID-19 pandemic, and for its contribution to strengthening the institutional and social response to this issue. The thesis is based on human rights, gender, intersectionality, and disability approaches, as well as theories on violence against women with disabilities, empowerment for the exercise of rights, strengthening of institutional capacities, and good management practices and trust, as a key factor in project management. The research employs a qualitative methodology and uses techniques such as semistructured interviews, document review, surveys, among others. The findings demonstrate the effectiveness of the project in empowering women with disabilities to exercise their right to a life free from violence, through an operational model that integrates the development of technical and personal skills, and psychological well-being. Likewise, the importance of the strategies implemented during the pandemic and the advocacy actions carried out by the women leaders, which show their empowerment to generate reforms and initiatives in the defense and recognition of their rights, are highlighted. However, challenges are identified in the application of knowledge by officials of the protection system, due to the high turnover in the context of political instability that the country is experiencing.